STR loci Penta D and Penta E: Data from a Northern Thai population sample - Bhoopat T. (2014)
We designed new primers that give shorter amplicons for Penta D and Penta E for easy separation on native polyacrylamide gels. 112 unrelated Northern Thai men were typed. A total of nine and eight-teen alleles was found for Penta D and Penta E, respectively. Both loci showed a high power of discrimination (Penta D: 0.927; Penta E: 0.966; both loci combined: 0.9975) as reported in other populations. Penta D met Hardy-Weinberg expectations, whereas Penta E did not, maybe because of the small sample size in relation to the large number of alleles of this locus. © 2004 Elsevier Ireland Ltd. All rights reserved.